Catalpol Attenuates Pulmonary Fibrosis by Inhibiting Ang II/AT1 and TGF-β/Smad-Mediated Epithelial Mesenchymal Transition - Yu, Qun; Zhu, Dewei; Zou, Yang; Wang, Kai; Rao, Peili; Shen, Yunhui (Frontiers in Medicine, 2022)
Idiopathic pulmonary fibrosis (IPF) is a tumor-like disease affecting over 3 million people worldwide with a high mortality rate and there are no effective drugs. Angiotensin II (Ang II), as a major effector peptide of the renin angiotensin aldosterone system (RAAS), has been shown to act in tandem with the transforming growth factor-β (TGF-β) signaling pathway to promote the infiltration of inflammatory cells, production of reactive oxygen species (ROS) and profibrotic factors after lung injury, and to participate in the process of epithelial mesenchymal transition (EMT). Catalpol (CAT) has been shown to have anti-inflammatory, antifibrotic, anticancer effects. We used bleomycin-induced mouse model of pulmonary fibrosis to evaluate the alleviation effect of CAT at 7d, 14d, 28d, respectively. The experiment proved that CAT might work through Ang Ⅱ/AT1/TGF-β/Smads pathway to ameliorate lung pathological changes as well as suppress EMT in mice with pulmonary fibrosis. CAT may serve as a novel therapeutic candidate for the simultaneous blockade of Ang II and TGF-β pathway to attenuate pulmonary fibrosis.